Does the recentivist philosophy “test” the antropic principle? - Czerny, Janusz (Folia Philosophica, 2001)
In the present paper the author attempts to analyse the main avowals and ideas contained within the anthropic principle on the basis of the theory of events elaborated by Józef Bańka. The task of such a "testing” of the anthropic principle with the theory of events is to gam its new elucidation. The result of the analyses is the principal conclusion that the main theses of the anthropic principle correspond to the conception of the theory of events.